What Court should be the competent one (in reason to the subject matter) when a civilly liable third party is involved? - Pérez-Prieto De Las Casas, Roberto (2015)
The New Peruvian Criminal Procedure Code includes the figure of the civilly liable third party, through which one or more subjects, who are civilly responsible together with the person who committed the crime, are involved in a criminalprocedure.The author of the present article analyses if it is correct to judge people who have not infringed Criminal Law, and hence should be judged in a civil procedure, through a criminal procedure because they are civilly responsible together withthe person that committed a crime. Further on, the author reflects on the fact that criminal judges have to sentence about topics of Civil Law.